2016
DOI: 10.1002/2016ja022863
|View full text |Cite
|
Sign up to set email alerts
|

The trailing edges of high‐speed streams at 1 AU

Abstract: The trailing‐edge rarefactions of 54 high‐speed streams at 1 AU are analyzed. The temporal durations of the trailing‐edge rarefactions agree with ballistic calculations based on the observed speeds of the fast and slow wind bounding the rarefactions. A methodology is developed to measure solar‐wind compression and rarefaction using the orientations of solar‐wind current sheets. One focus is to determine the signature that best describes the location of the trailing‐edge stream interface between coronal‐hole‐or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 138 publications
2
60
0
Order By: Relevance
“…Indeed as energy and momentum may be transferred across such boundaries, their structure should be better preserved in composition than, say, flow velocity. However, boundaries in ionisation state measurements are sometimes observed to be smoothed out at the trailing edge of solar wind streams, in a similar manner to velocity (Schwadron, 2005;Borovsky and Denton, 2016). Ko et al (2014) found O 7+ / O 6+ to be a better tracer of coronal origin than velocity observationally.…”
Section: Introductionmentioning
confidence: 91%
“…Indeed as energy and momentum may be transferred across such boundaries, their structure should be better preserved in composition than, say, flow velocity. However, boundaries in ionisation state measurements are sometimes observed to be smoothed out at the trailing edge of solar wind streams, in a similar manner to velocity (Schwadron, 2005;Borovsky and Denton, 2016). Ko et al (2014) found O 7+ / O 6+ to be a better tracer of coronal origin than velocity observationally.…”
Section: Introductionmentioning
confidence: 91%
“…The authors in that study identified an inflection point in the solar wind velocity as the best indicator of the fast‐to‐slow‐wind stream interface. Fluid simulations supported this parameter as marking the fast‐to‐slow transition based on pressure balance; see Borovsky and Denton [ Figures 11 and 12] for a detailed description of the fluid simulations. Based on the findings from that study, it is clear that during (and after) the arrival of trailing edges of HSSs in the vicinity of Earth, the magnetosphere will be bathed in a different type of solar wind, with different plasma parameters, than those which are encountered on the leading edge of HSSs.…”
Section: The Solar Wind Properties Of Trailing Edges Of Hsssmentioning
confidence: 99%
“…Figure contains a schematic diagram of the solar wind velocity during the passage of a single HSSs, including the location of the compression region (CIR) on its leading edge and rarefaction region on its trailing edge (see also Figures 1, 2, and 5 from Borovsky and Denton []). The precise location of the interface between fast plasma that is of coronal‐hole origin and slow plasma that originates in the streamer belt is generally straight‐forward to identify on the leading edge of a HSS (e.g., the east‐west flow deflection in the solar wind velocity), and challenging to identify on the trailing edge of a HSS.…”
Section: The Solar Wind Properties Of Trailing Edges Of Hsssmentioning
confidence: 99%
See 2 more Smart Citations